Facile preparation of polymer-grafted ZIF-8-modified magnetic nanospheres for effective identification and capture of phosphorylated and glycosylated peptides - Yi, Linhua; Yan, Yinghua; Tang, Keqi; Ding, Chuan-Fan (Analytical methods, 2020)
As a member of MOFs, Zn-MOFs (ZIF-8) are seldom used in phosphopeptide enrichment because ZIF-8 is soluble in acid solutions. Therefore, properly designing a novel strategy to overcome the defect of ZIF-8 is necessary. In this study, a novel multifunctional nanoprobe was designed by uniting magnetic core, titania shell and hydrophilic metal-organic frameworks (named as Fe 3 O 4 @PDA@mTiO 2 @PEI- g -ZIF-8). Integrating the strategies of hydrophilic interaction affinity chromatography (HILIC), immobilized metal ion affinity chromatography (IMAC) and metal oxide affinity chromatography (MOAC), the Fe 3 O 4 @PDA@mTiO 2 @PEI- g -ZIF-8 mesoporous microspheres can enrich phosphorylated peptides and glycosylated peptides simultaneously. Fe 3 O 4 @PDA@mTiO 2 @PEI- g -ZIF-8 has high selectivity (maximum molar ratio β-casein/HRP : BSA = 1 : 1000), low detection limit (2 fmol) towards phosphopeptides and glycopeptides. Besides, the Fe 3 O 4 @PDA@mTiO 2 @PEI- g -ZIF-8 also exhibited a fine performance in the actual sample detection. In the experiment, taking saliva as a sample, 16 phosphorylated peptides were identified, and from a human serum sample, 4 phosphorylated peptides were selectively identified. All in all, the materials show great potential in the future study of phosphoproteomics and glycoproteomics. As a member of MOFs, Zn-MOFs (ZIF-8) are seldom used in phosphopeptide enrichment because ZIF-8 is soluble in acid solutions.